Preimplantation genetic diagnosis for cystic fibrosis: the Montpellier center's 10‐year experience. (20th May 2014) - Girardet, A.; Ishmukhametova, A.; Willems, M.; Coubes, C.; Hamamah, S.; Anahory, T.; Des Georges, M.; Claustres, M.
<x xml:space="preserve">Abstract</x> This study provides an overview of 10 years of experience of preimplantation genetic diagnosis (PGD) for cystic fibrosis (CF) in our center. Owing to the high allelic heterogeneity of CF transmembrane conductance regulator (CFTR) mutations in south of France, we have set up a powerful universal test based on haplotyping eight short tandem repeats (STR) markers together with the major mutation p.Phe508del. Of 142 couples requesting PGD for CF, 76 have been so far enrolled in the genetic work‐up, and 53 had 114 PGD cycles performed. Twenty‐nine cycles were canceled upon in vitro fertilization (IVF) treatment because of hyper‐ or hypostimulation. Of the remaining 85 cycles, a total of 493 embryos were biopsied and a genetic diagnosis was obtained in 463 (93.9%), of which 262 (without or with a single CF‐causing mutation) were transferable. Twenty‐eight clinical pregnancies were established, yielding a pregnancy rate per transfer of 30.8% in the group of seven couples with one member affected with CF, and 38.3% in the group of couples whose both members are carriers of a CF‐causing mutation [including six couples with congenital bilateral absence of the vas deferens (CBAVD)]. So far, 25 children were born free of CF and no misdiagnosis was recorded. Our test is applicable to 98% of couples at risk of transmitting CF.